The impact of tax techniques on the quality of services provided to income taxpayers: An exploratory study in a sample of the branches of the General Tax Authority / Baghdad Governorate (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to demonstrate the impact of tax techniques on the quality of services provided to income taxpayers by studying the correlational and influencing relationships between the exploited variable (tax techniques) and the dependent variable (the quality of services provided to income taxpayers), and in line with the research objectives, the main hypothesis of the research was formulated (there is a relationship Significance between tax techniques and the quality of services provided to income taxpayers) a number of sub-hypotheses emerged from this hypothesis that were stated in the research methodology, and a number of conclusions were reached, the most important of which were (through the use of the correlation coefficient at the level of significance (0.05) and the degree of freedom (28). According to the (T) test, it was found that there is a significant relationship between tax techniques, which are technology, hardware, people, communication networks, database, software and the quality of services provided to income taxpayers) and based on the research findings, the researcher recommends a set of recommendations, the most important of which is (focusing on addressing Weaknesses in the variables or elements of tax techniques that were clarified by analyzing the results of the questionnaire in a way that helps improve the quality of services provided to taxpayers.